The Jewish calendar controversy of 921/2 CE - Stern, Sacha (Time, Astronomy, and Calendars, 2019)
"In the year 921/2, the Jewish leaders of Palestine and Babylonia disagreed on how to calculate the calendar. This controversy led to the celebration of Passover and other festivals, through two years, on different dates. Although the whole Jewish Near East was drawn into the controversy, it was later forgotten, until its 19th-century rediscovery in the Cairo Genizah. The faulty editions of these texts have led to much misunderstanding about the nature and aftermath of the controversy. In this book, Sacha Stern re-edits completely the texts, discovers many more, and challenges the consensus on the controversy's history. This book sheds light on medieval Rabbanite relations, and on the processes that brought about the standardization of the calendar in medieval Jewry."